Financial Development: The Role of GDP per Capita Dynamics in Low- & Middle-Income Economies - Kapaya, Saganga Mussa (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2023)
This study delves into the complex role of economic growth on financial development within low- and middle-income economies (LMIE). It analyzes a dataset spanning 85 countries from 1980 to 2020, collapsed into 9 periods, yielding 765 observations. Employing General Method of Moments (GMM), including two-step system GMM and forward-orthogonal deviations IV/GMM methods, the research uncovers intriguing dynamics. Positive shifts in GDP per capita are found to correspond with heightened financial development, whereas negative changes exhibit an adverse relationship. Government consumption yields mixed results, and inflation negatively impacts financial development, while trade openness and favorable terms of trade exhibit positive associations. These findings underscore the significance of economic development, price stability, trade openness, and financial sector stability in nurturing financial development in LMIE. Therefore, policymakers are encouraged to prioritize strategies aimed at fostering economic growth, income augmentation, and economic resilience, particularly in times of economic turmoil. This research offers a unique contribution by dissecting economic growth into positive and negative changes, providing insights into their distinct impacts on financial development using GMM estimation. It empowers policymakers to leverage economic growth shifts and trade reforms for inclusive financial development.